2014
DOI: 10.1016/j.tim.2014.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Long-lived reservoirs of HIV-1

Abstract: HIV-1 persistence in long-lived cellular reservoirs remains a major barrier to a cure. In a recent Nature Medicine paper, Buzon et al. identify memory T cells with stem cell-like properties (TSCM) that harbor infectious provirus and that likely contribute to HIV-1 persistence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…However, the persistence of latent reservoirs of replication-competent non-induced proviruses remains a major obstacle in HIV-1 eradication [ 3 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. These latent reservoirs are established early during acute viral infection [ 17 , 18 , 19 ]. Macrophages and latently infected resting CD4+ T cells are reservoirs of HIV-1 [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the persistence of latent reservoirs of replication-competent non-induced proviruses remains a major obstacle in HIV-1 eradication [ 3 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. These latent reservoirs are established early during acute viral infection [ 17 , 18 , 19 ]. Macrophages and latently infected resting CD4+ T cells are reservoirs of HIV-1 [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reports suggest the HIV-1 infection of circulating monocytes in vivo. The infected monocytes can cross the blood-tissue barrier and can differentiate into macrophages [ 18 , 26 , 37 , 38 , 39 ]. Moreover, HIV-1 infected macrophages release several immunoregulatory and inflammatory cytokines including TNF-α, interleukin (IL)-1, and IL-7, which in turn influence viral replication and disease associated with viral infection [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…CCR5 is an ideal target for Studies have indicated that the CCRT antagonist combined with HAART treatment can shrink the latent virus [28] , but whether will it apply to the large sample. that needs further study cannot clear it [29,30] .…”
Section: Ccr5 Antagonist Of Chemokine Receptormentioning
confidence: 97%
“…ART results in undetectable viremia in the plasma of HIV+ individuals but fails to achieve complete virus eradication, hence requiring life-long treatment [ 1 , 2 •, 3 7 ]. HIV persistence is explained by the existence of reservoirs that are established early upon HIV exposure [ 8 ••, 9 11 ]. Two types of reservoirs have been described that are not mutually exclusive and that are likely to co-exist in some individuals.…”
Section: Hiv Latencymentioning
confidence: 99%